The Factors Influencing Competitive Advantage and Customer Satisfaction at PT Mitra Niaga Madani - Muhammad Ichwan; Agus Salim (Dinasti International Journal of Education Management And Social Science, 2025)
The aim of this study is to analyze the effect of product diversification and product quality on customer satisfaction with competitive advantage as a mediating variable at PT Mitra Niaga Madani (PT MNM). This study employs a quantitative descriptive approach with data collection through the distribution of questionnaires. The sample in this study consists of customers of PT Mitra Niaga Madani. The analysis used in this research is Structural Equation Modeling-Partial Least Squares (SEM-PLS) with the SmartPLS 3.0 application. PT Mitra Niaga Madani is engaged in services, trade, transportation, and industry. The business activities conducted include property rental services, property development, property trading, construction services (contractors), and trade related to property businesses. The results of the study show that product diversification and product quality have a significant positive impact on competitive advantage and affect customer satisfaction at PT MNM. This research is expected to provide valuable insights for PT MNM to enhance its competitiveness and achieve customer satisfaction, so that the company can remain competitive and grow in the construction industry. It is also hoped that this study will contribute to the development of management science, particularly for companies in the business context at PT MNM.